Calcium-dependent, non-apoptotic, large plasma membrane bleb formation in physiologically stimulated mast cells and basophils. Issue 1 (1st January 2019) - Jansen, C.; Tobita, C; Umemoto, E. U.; Starkus, J.; Rysavy, N. M.; Shimoda, L. M. N.; Sung, C.; Stokes, A.J.; Turner, H
ABSTRACT: Large membrane derangements in the form of non-detaching blebs or membrane protrusions occur in a variety of cell stress and physiological situations and do not always reflect apoptotic processes. They have been studied in model mast cells under conditions of cell stress, but their potential physiological relevance to mast cell function and formation in primary mast cells or basophils have not been addressed. In the current study, we examine the large, non-detaching, non-apoptotic, membrane structures that form in model and primary mast cells under conditions of stimulation that are relevant to allergy, atopy and Type IV delayed hypersensitivity reactions. We characterized the inflation kinetics, dependency of formation upon external free calcium and striking geometric consistency of formation for large plasma membrane blebs (LPMBs). We describe that immunologically stimulated LPMBs in mast cells are constrained to form in locations where dissociation of the membrane-associated cytoskeleton occurs. Mast cell LPMBs decorate with wheat germ agglutinin, suggesting that they contain plasma membrane (PM) lectins. Electrophysiological capacitance measurements support a model where LPMBs are not being formed from internal membranes newly fused into the PM, but rather arise from stretching of the existing membrane, or inflation and smoothing of a micro-ruffled PM. This study provides new insights into the physiological manifestations of LPMB in response to immunologically relevant stimuli and in the absence of cell stress, death or apoptotic pathways.